A Cross-Sectional Study about a Health Information System (HIS) in the United Arab Emirates Federal Healthcare Organization (UAE FHO) - Abdool, Shaikha Abdulkarim (2014)
As healthcare organizations world-wide competing to provide the ultimate care as easy as possible to its customers, IT technologies have been embraced in delivering healthcare in various ways, such as: in diagnosing diseases, treatment and for research and planning purposes. Health information system (HIS) is part of IT technologies that most if not all healthcare organizations globally are moving toward implement it. Because of that a cross-sectional study was conducted about health information system (HIS) in the United Arab Emirates (UAE) Federal Health Organization. The aims of this research were to identify the current status of the health information system (HIS) in the UAE Federal Health Organization (UAE FHO) and how health information system (HIS) can help in re-designing patients’ care pathway as well as improving health outcomes. Another aim of this research was to identify the challenges faced in this system with possible solutions to overcome these challenges. Mainly, quantitative method was utilized to conduct the study. The response rate in this study was high and the results were overall positive. The study met its aims and covered the targeted research questions related to HIS. Two hypotheses were tested related to patients’ care pathway and health outcomes.